Hand antisepsis without decreasing efficacy by shortening the rub-in time of alcohol-based handrubs to 15 seconds. Issue 4 (April 2020) - Harnoss, J.C.; Dancer, S.J.; Kaden, C.F.; Baguhl, R.; Kohlmann, T.; Papke, R.; Zygmunt, M.; Assadian, O.; Suchomel, M.; Pittet, D.; Kramer, A.
Summary: Background: A previous study among neonatal intensive care unit (NICU) nurses showed that the antibacterial efficacy of alcohol-based handrubs (ABHR) can be achieved in 15 s instead of 30 s with a significant increase in the frequency of hand antisepsis. This study aimed to examine 15-s vs 30-s antisepsis performance by measuring microbial load on fingertips and compliance among nurses in a low-risk gynaecological ward. Methods: An independent trained observer monitored the frequency and compliance with hand antisepsis during shifts in a crossover design. Fingertips including thumbs were rinsed in soy broth before hand rubbing at the beginning of a shift and then hourly to determine the bacterial load. Performance activity was assigned to the contamination class of the Fulkerson scale. Immediately before the lunch break, volunteers cleaned their hands for a randomly determined application time of 15 or 30 s. Results: Examination of bacterial load on fingertips revealed no difference between 15 vs 30 s application time. Controlled hand antisepsis before the lunch break also showed no difference in efficacy for either test series. Participants rubbing for 15 s were more likely to perform hand antisepsis compared with those rubbing for 30 s ( P =0.2). The compliance increased from 54.7% to 69.5% in the 15-s trial. Discussion: Shortening the duration for hand antisepsis did not decrease efficacy. Shortening the application time to 15 s should be considered within the critical components of a successful multimodal intervention strategy to improve hand-hygiene compliance in clinical practice.